Сучасний стан і тенденції розвитку ринку молока Запорызької області - Куліш, Тетяна Володимирівна; Кулиш, Татьяна Владимировна; Kulish, Tetiana (КНЕУ, 2015)
UK: У статті проведено аналіз стану ринку молока Запорізької області. Виявлено основні проблеми формування пропозиції на ринку молока. Визначено роль держави в створенні конкурентних умов функціонування на ринку молока та молочної продукції. Запропоновано можливі шляхи вирішення проблем галузі, які сприятимуть підвищенню їх конкурентоспроможності на внутрішньому та міжнародному ринках. RU: В статье проведен анализ состояния рынка молока Запорожской области. Выявлены основные проблемы формирования предложения на рынке молока. Определена роль государства в создании конкурентных условий функционирования на рынке молока и молочной продукции. Предложены возможные пути решения проблем отрасли, которые будут способствовать повышению их конкурентоспособности на внутреннем и международном рынках. EN: The article analyzes the state of the dairy industry of Zaporozhe region, monitored the production of the milk in the last five years. The main problems of the formation of market milk supply, analyzed problems in the functioning of the processing enterprises of the dairy industry. Shows the problem of low level of technical equipment and agricultural milk processing plants. Described the role of the state in creating a competitive environment for the functioning of the market of milk and milk products. Proposes measures to improve the mechanism of state support for milk producers and processors. The possibilities of vertical integration of agricultural producers and milk processors in the industry/ The possible ways to solve problems in the industry, which will help them improve their competitiveness in the domestic and international markets.
Keywords: ринок молока; сільськогосподарські підприємства; галузь; конкурентоспроможність; ефективність; прибуток; рынок молока; сельскохозяйственные предприятия; отрасль; конкурентоспособность; эффективность; прибыль; milk market; agricultural enterprises; industry; competitiveness; efficiency; profit